2023
DOI: 10.1002/batt.202200491
|View full text |Cite
|
Sign up to set email alerts
|

On the Reversible Sodium Plating/stripping Reaction in Porous SiCN(O) Ceramic: A Feasibility Study

Abstract: Sodium‐ion batteries (SIBs) are a cost‐effective and sustainable alternative to lithium‐ion batteries (LIBs), which might be independent of rare raw materials. These advantages come at the expense of low energy density. Sodium metal batteries (SMBs) can provide a possible solution. In this work, we present the use of a porous silicon carbonitride (SiCN(O)) ceramic as an anodic matrix for reversible Na‐plating. The role of the pores is investigated and the plating mechanism allowing reversible and uniform plati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…[5] Numerous studies have addressed their functionality and demonstrated their suitability for both lithiumbased [6][7][8][9][10][11][12] and sodium-based batteries. [13][14][15][16][17] Among them, silicon oxycarbonitride (SiCN(O)) has attracted attention due to its ability to serve as a porous matrix for reversible plating of metallic sodium on its surface. [18] This class of ceramic materials possess a complex structure comprising a ceramic matrix containing embedded "free carbon" phase.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Numerous studies have addressed their functionality and demonstrated their suitability for both lithiumbased [6][7][8][9][10][11][12] and sodium-based batteries. [13][14][15][16][17] Among them, silicon oxycarbonitride (SiCN(O)) has attracted attention due to its ability to serve as a porous matrix for reversible plating of metallic sodium on its surface. [18] This class of ceramic materials possess a complex structure comprising a ceramic matrix containing embedded "free carbon" phase.…”
Section: Introductionmentioning
confidence: 99%